A microbiota do Rio Ituqui a partir do DNA ambiental: saberes e costumes tradicionais aliados à ciência - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
For a long time microorganisms, in different analyses, were associated only with negative aspects. However, it is now known that many microorganisms produce substances that are beneficial and end up contributing to the improvement and quality of the ecosystem. The objective of the research is to analyze the socio-environmental quality of the water under consideration with its different uses by the quilombola community of Ituqui through taxonomic identification using environmental DNA (eDNA) techniques. For this, the methodology is based on the use of environmental DNA, which is a non-invasive technique that detects the DNA of species in samples, allowing the identification of species without capturing them, this, together with the perception of the quilombola community, through field work, interviews and questionnaire applications. The water samples were collected and filtered, and eDNA was obtained from the filters, which was sequenced using the Next Generation Sequencing technique. The analysis of the data obtained showed that the water from the Ituqui River is safe for consumption by the community, as pathogenic microorganisms were not identified. However, it is necessary to return to the community during the flood period to carry out a new assessment, comparing it with the data from this research, so that we can confirm whether the use of river water is really safe.
Keywords: Água; Qualidade Ambiental; eDNA; Comunidade Quilombola; CNPQ:: CIÊNCIAS BIOLÓGICAS